Current Issues of the ‘Hungarian Euro’ with Special Regard to the Self-set ‘Maastricht 2.0’ Criteria - Marinkás, György (Maastricht 30: A Central European Perspective, 2025)
The author strives to answer why Hungary stayed out of the Eurozone so far and if there is any chance of a nearby accession. In order to do so, in the first part the author introduces the opinions of high-ranking officials and the Hungarian convergence data from the last twenty years. In this regard, the author provides an insight how the political will and the economic possibilities did not collide: as a Hungarianpeculiarity while there was a political will in the 2000s to access, the economic situation did not allow it. The situation has been the opposite in the last years: in the author’s view, between 2014 and 2020 Hungary would have had the opportunity to access the eurozone with a little extra effort exerted, however, it was not on the top of the priority list. Last, but not least, the author introduces the consequences of the decision of the drafters of the Fundamental Law to grant constitutional rank to theforint as the legal tender of Hungary. In the second part, the author provides a brief introduction of the ‘post-Eurozone debt crisis’ regulatory choices of the EU legislator – namely the creation of the Banking Union – and also the choices of the Hungarian legislator on the nexus between the Hungarian Central Bank and the institutions of the Banking Union. This way, the author can make conclusions on the maturity of the Banking Union’sinstitution and their functioning and evaluate the earlier arguments in the studies issued under the aegis of the HCB, namely that the rules of the Banking Union are unclear and their functioning displays uncertainty. The author also provides a comparison of the chosen crisis management tools of the ECB and the HCB related to three crises, namely: the Euro-zone debt crisis, the COVID-19-related crisis and theRusso-Ukrainian War related crises. The author concludes on the chosen crisis management tools of the ECB and the HCB, highlighting the similarities and differences. Keywords: Hungarian Central Bank, monetary policy, convergence criteria, real convergence, Maastricht 2.0, Economic and Monetary Union, Eurozone, Banking Union, COVID-19, Russo–Ukrainian War